2021
DOI: 10.3389/fnagi.2021.718850
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Δ9 -Tetrahydrocannabinol (THC) Alone or in Combination With a 1:1 Ratio of Cannabidiol (CBD) in Reversing the Spatial Learning Deficits in Old Mice

Abstract: Decline in cognitive performance, an aspect of the normal aging process, is influenced by the endocannabinoid system (ECS). Cannabinoid receptor 1 (CB1) signaling diminishes with advancing age in specific brain regions that regulate learning and memory and abolishing CB1 receptor signaling accelerates cognitive aging in mice. We recently demonstrated that prolonged exposure to low dose (3 mg/kg/day) Δ9-tetrahydrocannabinol (THC) improved the cognitive performances in old mice on par with young untreated mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In this regard, the THC doses used in this study were much lower than the dose that could induce the anxiety-like behavior in mice. Contrary to common belief, a handful of preclinical studies have revealed the beneficial effect of in vivo THC treatment at doses ranging of 0.002 and 3 mg/kg against the age-related decline in cognitive performance of aged mice [ 25 , 26 , 27 ]. Unlike the documented in vivo studies [ 25 , 26 , 27 ], the present study was carried out on aged APP/PS1 mice, and the animals were treated with 0.02 and 0.2 mg/kg of THC once every other day, which were lower than the doses of 1 and 3 mg/kg/d reported by Zimmer’s group [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, the THC doses used in this study were much lower than the dose that could induce the anxiety-like behavior in mice. Contrary to common belief, a handful of preclinical studies have revealed the beneficial effect of in vivo THC treatment at doses ranging of 0.002 and 3 mg/kg against the age-related decline in cognitive performance of aged mice [ 25 , 26 , 27 ]. Unlike the documented in vivo studies [ 25 , 26 , 27 ], the present study was carried out on aged APP/PS1 mice, and the animals were treated with 0.02 and 0.2 mg/kg of THC once every other day, which were lower than the doses of 1 and 3 mg/kg/d reported by Zimmer’s group [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to common belief, a handful of preclinical studies have revealed the beneficial effect of in vivo THC treatment at doses ranging of 0.002 and 3 mg/kg against the age-related decline in cognitive performance of aged mice [ 25 , 26 , 27 ]. Unlike the documented in vivo studies [ 25 , 26 , 27 ], the present study was carried out on aged APP/PS1 mice, and the animals were treated with 0.02 and 0.2 mg/kg of THC once every other day, which were lower than the doses of 1 and 3 mg/kg/d reported by Zimmer’s group [ 25 , 26 ]. Results of our study confirmed that aged APP/PS1 mice exhibited significantly elevated Aβ production and impaired spatial memory that recapitulated the early-stage AD in humans ( Figure 3 , Figure 4 and Figure 5 and Figure 6 C–G), suggesting that aged APP/PS1 mice are a better model than aged wild-type mice for evaluating the potential of THC in the treatment of AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low doses of THC have been employed to reach this goal, i.e., to improve the cognitive performance of aged mice. Interestingly, while Bilkei-Gorzo [62] and Nidadavolu [63] obtained this result after chronic treatment, Sarne [64] demonstrated the positive effect of a single ultralow dose of THC (0.002 mg/kg) in aged female mice that lasted at least 7 weeks. They suggested that a single dose of THC was able to induce long-lasting structural alterations, likely through the involvement of Sirtuin-1, a protein deacetylase that was shown to be involved in synaptic plasticity, memory formation, learning capability, neuronal development, and neuroprotection, and that was found decreased in old mice [64].…”
Section: Effects Of Cannabinoid Exposure In Older Animalsmentioning
confidence: 96%
“…According to this hypothesis, the paucity of papers investigating the effect of modulation of the endocannabinoid system in aged rodents seems to suggest that replenishing the lost endocannabinoid signaling would be beneficial to slowing down the physiological aging process (Table 4) [62][63][64]. Low doses of THC have been employed to reach this goal, i.e., to improve the cognitive performance of aged mice.…”
Section: Effects Of Cannabinoid Exposure In Older Animalsmentioning
confidence: 99%